Reasons of Social Media Addiction among Youth: An Exploratory Study - Pallathadka, Harikumar; Pallathadka, Laxmi Kirana; Devi, Shoraisam Kiranbhala (Integrated Journal for Research in Arts and Humanities, 2022)
Social networking sites are technological platforms that facilitate the advent and sharing of emotions, interests, information, ideas, and various types of expressions in the virtual world of groups, communities, or networks. Youth are the most significant patrons of social media. They are so fascinated by social media that they cannot reduce or limit their intake of online media. Youth dependency on social media (like Facebook, Instagram, Twitter, and WhatsApp) is characterized by the aggregate of an immoderate media intake and a growing trust in social media to sense good and an incapability to forestall or cut down. Addiction to social media has positive uses also, like making consumers globalize, presenting real-time communication, etc. This paper aims to understand the addiction to social media amongst youth. It additionally describes the signs and symptoms of dependency on social media. Also, understand the behavioral association between social media dependency and mental fitness or the overall instructional performance of youth. A sample of 133 respondents was collected through a "standard questionnaire," which was created on a five-point interval scale.